2015
DOI: 10.1007/978-3-319-17121-0_81
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid Hormone Signaling and Cone Photoreceptor Viability

Abstract: Thyroid hormone (TH) signaling regulates cell proliferation, differentiation, and apoptosis. In the retina, TH signaling plays a central role in cone opsin expression. TH signaling inhibits S opsin expression, stimulates M opsin expression, and promotes dorsal-ventral opsin patterning. TH signaling has also been associated with cone photoreceptor viability. Treatment with thyroid hormone triiodothyronine (T3) or induction of high T3 by deleting the hormone-inactivating enzyme type 3 iodothyronine deiodinase (D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 29 publications
1
10
0
Order By: Relevance
“…A recent study showed that suppressing thyroid hormone signaling could preserve cone photoreceptors in animal models of macular degeneration [ 13 ]. By contrast, administration of high doses of the thyroid hormone triiodothyronine caused cone photoreceptor death in animal models, and deletion of the thyroid hormone receptor gene could reverse this effect [ 14 ]. In a prospective cohort study, Chaker et al discovered that higher free thyroxine levels were associated with an increased risk of AMD [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study showed that suppressing thyroid hormone signaling could preserve cone photoreceptors in animal models of macular degeneration [ 13 ]. By contrast, administration of high doses of the thyroid hormone triiodothyronine caused cone photoreceptor death in animal models, and deletion of the thyroid hormone receptor gene could reverse this effect [ 14 ]. In a prospective cohort study, Chaker et al discovered that higher free thyroxine levels were associated with an increased risk of AMD [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…In a prospective cohort study, Chaker et al discovered that higher free thyroxine levels were associated with an increased risk of AMD [ 15 ]. These studies suggested that using levothyroxine, which is also employed in thyroid suppression therapy usually administered to thyroid cancer patients, would increase the risk of AMD [ 10 , 11 , 12 , 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the retina, developmental hypothyroidism causes a reduction of retinal progenitor cells, reduced retinal thickness, altered photoreceptor patterning, improperly formed photoreceptor outer segments, and reduced cell density in the retinal ganglion cell layer (Navegantes et al, 1996, Ng et al, 2001, Sevilla-Romero et al, 2002, Harpavat and Cepko, 2003, Roberts et al, 2006, Ng et al, 2011, Pinazo-Duran et al, 2011, Ma and Ding, 2016. Post-mitotic retinal precursor cells differentiate into all types of photoreceptors including rods, middlewavelength sensitive (M, "green") cones, short-wavelength sensitive (S, "blue") cones.…”
Section: Introductionmentioning
confidence: 99%
“…When TH deiodination is impaired by iopanoic acid treatment, T 3 treatment further enhances the deleterious eye phenotype, revealing a crucial role for thra as aporeceptor and pinpointing that TH availability is tightly controlled [ 4 ] during eye development. D3 plays an essential protective role in inhibiting TH-induced proliferation in CMZ, resulting in an asymmetric growth in Xenopus laevis retina during metamorphosis [ 13 , 11 ], or in protecting certain photoreceptors from excessive T 3 signaling in the mouse and zebrafish retina [ 5 , 12 , 14 ]. These findings favor the hypothesis of a control of local TH availability mostly by the inactivating deiodinase D3.…”
Section: Introductionmentioning
confidence: 99%
“…As to other species, the role of TH on retinal development has been addressed during embryogenesis in rodents [ 10 , 14 ], during pro-metamorphosis in fish [ 5 ] as well as during metamorphosis in Xenopus [ 4 , 11 ].…”
Section: Introductionmentioning
confidence: 99%